Exploring empathy, communication, and cultural competence in low back pain care: a comparative cross-sectional study of nurses and physicians in Israel - Nikolova, Silviya; Gotani, Aiham (Frontiers in Communication, 2025)
BackgroundEffective communication is critical in managing chronic low back pain, yet disparities exist in how healthcare professionals engage with patients. This study aimed to identify professional differences in relational and culturally responsive approaches to caring for patients with low back pain in Israel.MethodsA cross-sectional study was conducted at Ziv Medical Center in Safed, Northern Israel, involving 50 healthcare professionals—31 nurses and 19 physicians —who manage patients with low back pain in various clinical settings. Participants completed a structured Likert-scale questionnaire evaluating four key aspects of communication: empathy, patient engagement, shared decision-making, and cultural competence. Data were analyzed using Jamovi (version 2.6.23), and group differences between nurses and physicians were assessed using the Mann–Whitney U test.FindingsNurses exhibited higher empathy and communication skills compared to physicians, particularly in emotional support, patient reassurance, and encouraging patient concerns (p < 0.05). Physicians, however, excelled in clinical decision-making and providing detailed explanations of treatments (p < 0.05). A significant positive correlation was found between empathy and communication skills for both groups (r = 0.62, p = 0.004). Nurses demonstrated higher cultural competence and provided more culturally tailored care, with a positive correlation between cultural competence and individualized care (r = 0.58, p = 0.009).Discussion and conclusionsThe study underscores the critical role of both nurses and physicians in shaping patient care experiences. Nurses tend to excel in empathy and communication, whereas physicians primarily focus on clinical decision-making and treatment. The observed correlation between cultural competence and patient reassurance suggests that greater cultural sensitivity may enhance the patient experience and strengthen trust within the care relationship. These findings highlight the need for targeted training to improve communication, empathy, and cultural awareness across healthcare teams, thereby fostering stronger collaboration and more effective patient care.